Community Relations: Bentuk Tanggung Jawab Sosial Organisasi - Yudarwati, G. Arum (Jurnal Ilmu Komunikasi, 2004)
Â Community relations is performed as an institutionâs planned, active, and continuing participation with and within a community to maintain and enhance its environment to the benefit of both the institution and the community. Community relations will reduce conflict and help to discover the best policy that lead to wellbeing community through the establishment of social capital as part of corporate social responsibility. At the macro level, the system approach and communitarian approach give perspectives to explain the interaction between organization with its environment. At the mezzo level, the community relations should be supported by its function in organization. Finally at the micro level, public relations practitioners should take a significant role in organizations.